The Effect of Compensation and Training on Employee Performance - Daniel Yusuf; Eliakim Purba; Putra Chairy (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of compensation and training on employee performance at PT Medan Mitra Auto either partially or simultaneously. The research method used in this research is the quantitative descriptive method. The population in this research is all employees of PT Medan Mitra Auto which amounted to 57 people, sampling technique in this research used a saturated sample technique. Data analysis technique uses classical assumption test, and multiple linear regression analysis, while hypothesis testing uses partial test and simultaneous tes. The results showed that partial compensation and training affect the performance of employees. Simultaneously compensation and job stress affect the employee's performance. The amount of coefficient of determination of 0.637this ability of variable compensation and training on employee performance variable equal to 63,7%. While the rest of 36.3% influenced other independent variables that are not examined in this study such as work conflicts, work stress, organizational commitment, motivation, work environment, and others.